Pengaruh Regulasi Emosi dan Persepsi Dukungan Sosial terhadap Stres Akademik Mahasiswa yang Sedang Menyusun Skripsi - Intan Salfina; Fadhilla Yusri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Academic stress among senior undergraduates is a common problem resulting from the demands of completing a thesis, academic pressure, and uncertainty about the future. These conditions can affect students’ mental health, motivation to learn, and academic success. This study aims to determine the influence of emotional regulation and perceptions of social support on the academic stress of students currently writing their theses. The research method employed a quantitative approach with a cross-sectional survey design. The sample consisted of 197 active undergraduate students currently working on their theses, selected using accidental sampling. Data collection was conducted via Google Forms using the Student-life Stress Inventory (SIS), the Emotion Regulation Questionnaire (ERQ), and the Multidimensional Scale of Perceived Social Support (MSPSS). Data analysis used multiple linear regression with the assistance of IBM SPSS Statistics 22. The results showed that emotion regulation did not have a significant effect on academic stress with a significance value of 0.924, while perceived social support had a significant effect with a significance value of 0.008. Simultaneously, both variables contributed 3.6% to students’ academic stress. In conclusion, social support plays a more important role in reducing academic stress among senior students compared to emotional regulation.